The Impact of Azerbaijan’s Oil Strategy on Economic Growth: Analysis and Diagnosis - Humbatova, Sugra; Panahova, Gunay. M.; Mahmudova, Ilhama Mahammadnabi; Hajiyev, Natig Gadim−Oglu (International Journal of Energy Economics and Policy, 2023)
The article considers the balance of hydrocarbon resources controlled by Azerbaijan, which gained independence in the 1990s, the extent of their utilization, and the potential that can be harnessed within our country’s existing capabilities, given the need to develop a qualitatively new oil strategy. In particular, in order to attract available resources into economic circulation, Azerbaijan signed the “Deal of the Century” with the world’s leading foreign oil companies due to a lack of sufficient financial, scientific−technical, technical−technological, investment−innovation potential for extracting and transporting oil from the deep seabed. Further, it assesses and rates in light of global experience and country reality concerning the effective use of oil money, and the structure of revenues and expenditures of the State Oil Fund of Azerbaijan (SOFAZ) for 2001−2021 is examined using particular materials, taking into consideration the multiplier impact. The analysis is used to examine the role of transfers to the state budget in ensuring macroeconomic stability, strengthening financial provisions for economic growth, improving the national economy’s structure, and regional development, and concludes that the oil strategy implemented in our country will ensure long−term, dynamic economic growth. Then, using quarterly data for 2003Q03-2021Q01, this article examines the impact of transfers from the State Oil Fund to the state budget on GDP, in other words, the long-term and short-term relationships between these variables. In this research, the ARDL model was used to assess co−integration and short−term relationships. In addition, this study used the FMOLS, DOLS, and CCR co−integration equations to explore long−term coefficients between variables. Granger causation tests were performed, Granger causation analysis was assessed using the Wald test (short−term or weak causation, long−term causation, and both short−term and long−term causation or strong causal relationship). The study put forward a hypothesis about the impact of transfers on GDP. This hypothesis was confirmed.